2022
DOI: 10.1155/2022/5188584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Proteomic Analyses of Proinflammatory Cytokines in a Mouse Model of Liver Transplant Rejection

Abstract: Liver transplantation (LT) is an effective strategy for the treatment of end-stage liver disease, but immune rejection remains a significant detriment to the survival and prognosis of these LT patients. While immune rejection is closely related to cytokines, the cytokines investigated within previous studies have been limited and have not included a systematic analysis of proinflammatory cytokines. In the present study, we used a protein chip system and proteomics to detect and analyze serum proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Other inflammatory diseases related with CXCL family contain ovarian related inflammation, inflammatory bowel disease, organ transplants, vascular diseases and so on [67,[112][113][114].…”
Section: Cxcr8mentioning
confidence: 99%
“…Other inflammatory diseases related with CXCL family contain ovarian related inflammation, inflammatory bowel disease, organ transplants, vascular diseases and so on [67,[112][113][114].…”
Section: Cxcr8mentioning
confidence: 99%
“…Studies have confirmed the significant upregulation of CXCL8 in chronic antibody-mediated rejection after renal transplantation ( 55 ). In addition, in a mouse model of liver transplant rejection, CXCL2 is significantly elevated in serum, which is the gene most closely related to the functions of neutrophils ( 56 ).…”
Section: Discussionmentioning
confidence: 99%